Brief Overview of Corporate Governance Structures Within Premium Listed Companies іn Romania - І. Pop (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Proper corporate governance structures and principles guide companies towards financial health and lay down the blocks for a sustainable development of the private sector. Moreover, there is a widespread recognition and growing empirical evidence that strong fundamentals of governance are a condition for business benefits largely described by better management, effective boards, improved decision-making process, reduced risk, increased operational efficiency and valuations. Given that trust is a basic condition of functioning capital markets and corporate governance guarantees transparency, accountability and operational integrity, the aim of this present paper is to assess the conformity of the premium traded companies at the Bucharest Stock Exchange with its corporate governance code. The results of our empirical study reveal the ongoing concerns, focus and level of importance given to corporate governance structures and principles by the most trusted and profitable traded Romanian companies.